Structure, abundance and biomass size spectra of copepods and other zooplankton communities in upper waters of the Southwestern Atlantic Ocean during summer - Thompson, Gustavo Ariel (2013)
Little attention has been paid to small copepods and other zooplankton inhabiting pelagic ecosystems of the Southwestern Atlantic Ocean under the influence of the Antarctic Circumpolar Current circulation, despite their important role in the trophic chain and fisheries. This study gives a synoptic view (January 2001) of the micro and mesoplankton size fractions and normalized biomass size spectra (NBSS) in upper waters of five different ecological domains (shelf and oceanic Subantarctic and Antarctic waters) including the Brazil-Malvinas confluence (BMC). Copepods were always the main component of the zooplankton; the <300-μm fraction represented between 70 and 99% in terms of numbers and from 20 to 88% in terms of biomass. Other zooplankton contributed with <40% to total zooplankton densities, though showing some biomass peaks (>50%). Chlorophyll a, sea surface temperature and salinity were the environmental variables that best explained the distribution trend of zooplankton, mainly that of the <300-μm fraction. For all the domains, NBSS revealed flat slopes (-0.6 to-1), suggesting a higher proportion of large organisms than expected at equilibrium. A dome-shape feature was detected in the BMC. Total biomass and trophic levels of the system were related to the composition of the community and the hydrological conditions of the domains covered.